High Rickettsial Diversity in Rodents and Their Ectoparasites From the Central Highlands of Madagascar. Issue 2 (27th December 2021) - Rasoamalala, Fanohinjanaharinirina; Parany, Mamionah N J; Rahajandraibe, Soloandry; Rakotomanga, Malala N; Ramihangihajason, Tojo; Soarimalala, Voahangy; Boyer, Sébastien; Rajerison, Minoarisoa; Ramasindrazana, Beza
Abstract: Rickettsioses are among emerging infectious diseases around the world. In Madagascar, little information is available regarding Rickettsia (Rickettsiales: Rickettsiaceae) diversity and their potential impacts on public health. In fact, molecular screening of ectoparasites of mammals reported the presence of three species, Rickettsia africae, Rickettsia typhi, and Rickettsia felis . The present study aims to investigate the diversity of Rickettsia in small mammals and associated ectoparasites (fleas and ticks) using a molecular approach. In September and December 2016, fieldworks were undertaken in two districts of Madagascar to capture small mammals using standard traps (Tomahawk and Sherman traps) and collect associated ectoparasites. In total, 12 taxa of ectoparasites (5 flea and 7 tick species) were collected from 89 individuals of four species of terrestrial small mammals. Rickettsia spp. were molecularly identified in one specimen of Rattus rattus (Rodentia: Muridae), one specimen of Pulex irritans (Siphonaptera: Pulicidae) as well as four specimens of Ixodes cf. colasbelcouri (Ixodida: Ixodidae). This study showed the presence of three phylogenetically distinct taxa of Rickettsia in small mammals and their ectoparasites. The current study broadens our knowledge on the diversity of Rickettsia in the Central Highlands of Madagascar and highlights for the first time the presence of Ri. felis in R. rattus and in tick, I. cf . colasbelcouri in Madagascar. Additional studies are needed to have exhaustive information on Rickettsia in small mammals and their ectoparasites, to determine their pathogenicity as well as their potential effects on public health in order to update the national policy for the control of emerging infectious diseases in Madagascar.